The Unbearing Threat of Golden Crescent Areas Combating Cases of Small and Light Arms Trafficking as Organized Crime in India - Wahyu Putri, Ayukinanti; Medina Septa Salsabila; Haidar Chandra Adhiananto (Jurnal Transformasi Global, 2024)
Along with the easier exchange of information, people and goods between countries as a result of the rapid globalization, forms of crime in the international world also continue to grow at the same time. One of the transnational crimes that is of concern and is very difficult to deal with today is the Proliferation of Small Arms and Light Weapons. In this paper, the author identifies the activities, entities and impacts of Small Arms and Light Weapons transnational crimes in India. To overcome this, various efforts have been made by the Government of India, but there are still obstacles in its implementation caused by the weakness of law in India so that these criminal groups can operate easily and prolifically. Transnational crime activities in India can be explained through trends in the spread, identification of transnational crimes, identification of Models of Conditions and Models of Operations, as well as handling methods applied at global, regional to national levels. Keywords: Transnational Organized Crime; Small Arms and Light Weapons; India; Golden Triangle